O estado da arte da educação física na educação infantil - Padula, Tainá Davalle [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Early Childhood Education corresponds to the period of insertion of the child in Basic Education. The curricular organization of this teaching cycle does not occur through disciplines, but by areas of knowledge or, as indicated in the third version of BNCC, through fields of experience. In this sense, Physical Education, as well as other disciplines, must pass through these fields to contribute to the student's education in Early Childhood Education. Many researches have discussed the role of physical education for children, the training of teachers in this area and the different approaches used in pedagogical practice. In this way, the objective of this research was to carry out a state-of-the-art study to investigate what has been published about Physical Education in Early Childhood Education. In order to do this, we opted for the search of articles in seven national journals in the area of Physical Education, with a temporal cut from January 2007 to December 2016. We found 37 articles with this pedagogical theme, which were inserted into four categories defined according to the analysis of the title, abstract and keywords of the articles. The four categories (the presence of Physical Education in Early Childhood Education - curricular approach, games as educational resources, body, movement and motor intervention, teacher training and pedagogical practices) presented similar percentages of the total number of articles selected (30% 27%, 25% and 19%, respectively), showing a good distribution of the subtopics listed in the research. The results show the importance of Physical Education in the motor, cognitive, social and affective development of the individual in the infantile phase. And that the Physical Education, although present in the curriculum, is still being established as a curricular component and, according to the authors, its practice must consider the specificities of the children and seek for the appreciation of their...

A Educação Infantil corresponde ao período de inserção da criança na Educação Básica. A organização curricular desse ciclo de ensino não ocorre por meio de disciplinas, mas sim por áreas de conhecimentos ou como indicado na terceira versão da BNCC, por meio de campos de experiência. Nesse sentido, a Educação Física, assim como as demais áreas, deve perpassar por esses campos para contribuir com a formação do aluno na Educação Infantil. Desse modo, o objetivo dessa pesquisa foi realizar um estudo do tipo estado da arte para investigar o que tem sido publicado sobre Educação Física na Educação Infantil. Para isso optou-se pela busca de artigos em sete periódicos nacionais da área de Educação Física, tendo como recorte temporal o período de janeiro de 2007 até dezembro de 2016. Foram encontrados 37 artigos com essa temática, os quais foram inseridos em quatro categorias definidas de acordo com a análise do título, resumo e palavras-chave dos artigos. As categorias são: a presença da Educação Física na Educação Infantil - abordagem curricular; brincadeiras e jogos como recursos educativos; corpo, movimento e intervenção motora; formação de professores e práticas pedagógicas. Elas apresentaram porcentagens semelhantes na distribuição do número total de artigos selecionados (30%, 27%, 25% e 19%, respectivamente). Os principais resultados apontam a importância da Educação Física no desenvolvimento motor, cognitivo, social e afetivo do indivíduo na fase infantil e mostram que a Educação Física, apesar de presente no currículo, ainda está se estabelecendo como componente curricular e, segundo os autores, sua prática deve considerar as especificidades das crianças e buscar a valorização do potencial lúdico/criativo delas. Além disso, a atuação pedagógica do professor nesse campo tem papel fundamental na construção de autonomia e autoconfiança da criança
Keywords: Educação física - Estudo e ensino; Educação fisica (Pre-escolar) - Estudo e ensino; Educação física para crianças; Brincadeiras; Jogos; Professores - Formação